1971
DOI: 10.3171/jns.1971.35.5.0601
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysm on a persistent primitive trigeminal artery

Abstract: ~' The angiographic demonstration of a rare case of persistent trigeminal artery aneurysm is reported. The incidence of persistent trigeminal artery in the authors' series is 0.6%. Approximately 14% of patients with a persistent trigeminal artery also have an intracranial aneurysm. The embryology involved and related cases are reviewed. KEY WORDS persistent trigeminal artery earotieo-basilar anastomosistrigeminal artery aneurysm S

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1
3

Year Published

1977
1977
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(50 citation statements)
references
References 14 publications
0
42
1
3
Order By: Relevance
“…[8][9][10] Autopsy specimens of PPTA have shown atherosclerotic changes of the arterial wall, more in the proximal than the distal portion to the aneurysm, but histological studies have revealed no evidence of developmental pathological anomalies in the wall of the PPTA. 9) We speculate that the specific hemodynamics of the PPTA, which directly branches and receives significant blood flow from the internal carotid artery, may induce the formation of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10] Autopsy specimens of PPTA have shown atherosclerotic changes of the arterial wall, more in the proximal than the distal portion to the aneurysm, but histological studies have revealed no evidence of developmental pathological anomalies in the wall of the PPTA. 9) We speculate that the specific hemodynamics of the PPTA, which directly branches and receives significant blood flow from the internal carotid artery, may induce the formation of aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…The site of the aneurysm in our case was the curved trunk of the PPTA, as found in most other reported aneurysms of the PPTA trunk. 3,5,6,[8][9][10][11]13,17,18) Such characteristic anatomical findings of the aneurysms strongly suggest that high hemodynamic stress initiated aneurysm formation. However, whether small branching arteries from the PPTA at the site of the aneurysm were involved, and any congenital predisposition of the artery walls cannot be excluded because of the multiple aneurysms around the circle of Willis in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent primitive trigeminal artery (PPTA) is the most common embryological vascular remnant, 1,4) is located between the carotid and vertebrobasilar arteries, 17) and is recognized on 0.1-0.6% of cerebral angiograms. Saccular aneurysms associated with PPTA are very common, and account for 14-32% of all cerebral aneurysms.…”
Section: Introductionmentioning
confidence: 99%
“…Saccular aneurysms associated with PPTA are very common, and account for 14-32% of all cerebral aneurysms. 3,4,6,7,11,14) Most aneurysms associated with the PPTA are located at the bifurcation of the carotid artery and the PPTA, whereas aneurysms arising at the PPTA trunk are extremely rare. The deep location of PPTA trunk aneurysms renders direct surgery very difficult, 17,18) so endovascular treatment has been attempted.…”
Section: Introductionmentioning
confidence: 99%